In-silico Simulation of Indoor Panic Situations using Reactive Agents - Torres, Giorgio P. F. G.; Farago, Willian C.; Oliveira, Alcione de Paiva (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2013: Anais do VII Workshop-Escola de Sistemas de Agentes, seus Ambientes e AplicaçõesDO - 10.5753/wesaac.2013.33197, 2013)
Panic situations sadly happens frequently. Even in cases where there are people trained to deal with emergency situations, most people panic, resulting in possible tragedies. In this article, it is investigated how primitive agents, with low capacity for deliberation and limited perception of the environment, behave in a panic scene. We conducted a case study, taking as example the tragedy in Santa Maria, Rio Grande do Sul - Brazil, where a fire in a nightclub resulted in the deaths of 241 persons.